THE INFLUENCE OF HEALTH EDUCATION ON THE INTERACTIVE KNEE TO KNEE TECHNIQUE BY HEALTH CADRES ON MOTHERS' KNOWLEDGE ABOUT INFANT AND TODDLER DENTAL AND ORAL HEALTH - Zulfikri; M. Faisal; Ayu Mardian (LLDIKTI Wilayah X, 2025)
Background: Health cadres, as the forefront of improving the health of mothers, infants, and toddlers, still face challenges with the high prevalence of dental caries in children in Indonesia. One of the causes is the improper and inadequate behavior of mothers in maintaining their children's dental and oral health.Objective: To determine the effect of health education using the Interactive Knee to Knee Technique by health cadres on mothers' knowledge about dental and oral health in infants and toddlers. ethod: Trained cadres conducted health education sessions for mothers with infants and toddlers using the Interactive Knee to Knee Technique to improve their knowledge about dental and oral health care for infants and toddlers.Research Results: This study is a cross-sectional design with a